Narrative 'You' and 'I' in the opening of Oriana Fallaci's Un uomo - Gatt-Rutter, John (Spunti e Ricerche, 2016)
Oriana Fallaci makes great play with the second person in her narratives. But this feature of her writing has been subjected mostly to destructive criticism with little attention paid to its narratological implications. Pratolini's example in Cronaca familiare, where the narrator reconstructs the life of his dead brother, may have helped Fallaci in addressing Un uomo to her dead companion, though her highly dramatic and public tone could not be more different from that of Pratolini's narrator.